The effect of palm oil mill effluent (pome) on the consolidation behavior of compacted high-plasticity clay under elevated temperatures - Akbar Ramadhani, Ahmad; Rusdiansyah, (Technium: Romanian Journal of Applied Sciences and Technology, 2026)
Palm Oil Mill Effluent (POME), a byproduct of palm oil processing, is characterized by high concentrations of suspended solids, a brownish color, and discharge temperatures ranging from 80°C to 90°C. These elevated temperatures have the potential to alter the physical and mechanical properties of the subgrade soil in waste ponds. However, research addressing this issue remains scarce, particularly regarding the consolidation behavior of high-plasticity clay. This study investigates the alterations in consolidation parameters of high-plasticity clay saturated with POME. The experiments were conducted using a modified consolidation apparatus across a temperature range of 28°C to 90°C. The results indicate that saturating the soil with POME altered the soil classification from high-plasticity clay (CH) to low-plasticity clay (CL), leading to a significant reduction in the Plasticity Index from 39.15% to 16.22%. At an elevated temperature of 90°C, the POME-saturated soil exhibited an 85.40% increase in the Compression Index (Cc). Conversely, POME saturation reduced the Swelling Index (Cs) by 25.86% and decreased the Coefficient of Consolidation (Cv) by 25.42% compared to conditions saturated with clean water.